The Relationship Between The Prevalence of Head Lice Infestation with Hygiene and Knowledge Among The Rural School Children In Yogyakarta - Hemelamariae Munusamy; Elisabeth Elsa Herdiana Murhandarwati; Sitti Rahmah Umniyati (Pusat Kedokteran Tropis, 2011)
Introduction: Pediculosis capitis causes considerable social distress. Rural children are in great risk because they live in conditions where poor knowledge and hygiene are related to this matter. However, the prevalence of pediculosis capitis among school age children in rural area in Yogyakarta have not known yet.Objectives: The objective of this study is to find the prevalence of head lice infestation among the rural school children and associating it with hygiene and knowledge.Methods: This was a cross sectional study done in February 2011 in 2 primary public schools in the rural areas of Yogyakarta with 158 subjects age ranging from 8 to 16 years old. Questionnaires inclusive of hygiene and knowledge aspect were given prior to the gross visual head lice examination by trained personnel.Results: The prevalence of head lice infestation among the rural school children is 19.6%. There is no significant relationship between this with knowledge and hygiene.Conclusion: The prevalence of head lice infestation in rural school areas in Yogyakarta is 19.6%. There is no significant relationship between the prevalence of head lice infestation with hygiene and knowledge among the rural school children in Yogyakarta.Keywords: Pediculosis capitis, head lice infestation, hygiene, knowledge